ANALISIS KEBIJAKAN DEVIDEN PADA PERUSAHAAN PROPERTI DAN REAL ESTATE DI INDONESIA - Mrs Setianingsih (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
For companies going public, getting investor confidence is a must, because that's the main reason listed on stock exchange, and company should to provide benefits (dividends). Therefore, this study was conducted to analyze the devident policy in property and real estate companies in Indonesia. The property and real estate companies listed in ISSI Indonesia Stock Exchange Period 2007-2016, as many as 60 samples. The method of this research is the type of this research is descriptive quantitative. In this study the population is a property and real estate companies that have joined in ISSI in 2012 until 2016 amounted to 51 companies. Sampling is done based on purposive sampling method, with the method then that meets the criteria is PT Adhi Karya (Persero) Tbk, PT. Gowa Makassar Tourism Development Tbk, PT. Jaya Real Property Tbk, PT. Plaza Indonesia Realty Tbk, PT. Summarecon Agung Tbk, PT. Total Bangun Persada Tbk. This research uses the test of panel data regression model, hypothesis test (t-statistic test and Determination Coefficient test (R2) using Eviews 9 program. Based on hypothesis testing showed that Quick Ratio, Debt to Total Asset, Return On Asset simultaneously have 40,9% influence to profit growth, and Profit growth have influence 50,9% to Dividend Payout Ratio.